Pengaruh Edukasi Teknik Menyusui pada Ibu Nifas terhadap Efektifitas dalam Menyusui - Rauf, Efri Leny; Ali, Rizky Nikmathul Husna; Mulyaningsih, Sri; Alamri, Luthfia (Program Studi DIV Kebidanan Fakultas Ilmu Kesehatan Universitas Muhammadiyah Gorontalo, 2024)
The prevalence of exclusive breastfeeding in Indonesia still does not meet the Governmen’s target of 80%. Exclusive breastfeeding coverage in Gorontalo in 2022 is only 48.8%. Success in providing exclusive breastfeeding must be supported by effective breastfeeding. This research was conducted at RSIA Sitti Khadijah Gorontalo. The aim of this research was to determine the effect of education on breastfeeding techniques for postpartum mothers on breastfeeding effectiveness. This research design is quasi-experimental with a posttest only group design approach. The sample in this study was 28 people divided into 2 groups. This research uses a latch score observation sheet. The results of data analysis using the independent t-test statistical test showed that there was an influence of education on breastfeeding techniques for postpartum mothers on the effectiveness of breastfeeding with a p-value of 0.000. In conclusion, education on breastfeeding techniques can influence the effectiveness of breastfeeding in postpartum mothers.